(3cJGH aj GdJhMjOs - (3eMeO Hf YHO GdhgGH Hf SdjeGf GdJejej GdfLOj , J (B1206 (3g`s
(3ChdgG (B:s
(3SFd GdTjN eMeO QMeg Gddg JYGdi Yf eSGFd GdChdi CMGOjK GdhYO hGdhYjO hbhd hgH GHf efHg eaJGM GdLfI dG Edg EdG Gddg s
(3BNQgG (B:s
(3hTQM GdEeGe CHj GdMSf Ydi Hf Nda GdTgjQ HGHf HWGd GdeZQHi GdeGdci ENdGU GdJhMjO ddg GdPi dG Edg EdG gh dYHGOg hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHY hGdYTQhfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdEeHQhRjGfG (B(404 d) s
Keywords: (3GdJhMjO hGdedd hGdfMds